Republic of Kazakhstan : 2018 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that growth has strengthened in Kazakhstan supported by higher oil production and increased activity in trade and manufacturing. Robust exports have contributed to an improvement of the external current account. Inflation has declined and remained within the target band of the National Bank of Kazakhstan (NBK). This, along with anchoring of inflationary expectations, has allowed the NBK to undertake several interest rate cuts. Growth is expected to remain solid, although there are risks. Overall growth will likely slow as the increase of oil production moderates, but non-oil growth should increase further over the medium term, reflecting structural reforms and financial repair and deepening.